Intramyocardial inflammation predicts adverse outcome in patients with cardiac AL amyloidosis. (25th October 2017) - Siegismund, Christine S.; Escher, Felicitas; Lassner, Dirk; Kühl, Uwe; Gross, Ulrich; Fruhwald, Friedrich; Wenzel, Philip; Münzel, Thomas; Frey, Norbert; Linke, Reinhold P.; Schultheiss, Heinz‐Peter
Abstract : Aims: To evaluate the influence of endomyocardial biopsy (EMB)‐proven intramyocardial inflammation on mortality in patients with cardiac transthyretin amyloid (ATTR) or amyloid light‐chain (AL) amyloidosis. Methods and results: We included 54 consecutive patients (mean age 68.83 ± 9.59 years; 45 men) with EMB‐proven cardiac amyloidosis. We followed up patients from first diagnostic biopsy to as long as 36 months (mean 11.5 ± 12 months) and compared their outcome with information on all‐cause mortality with or without proof of inflammation on EMB. Intramyocardial inflammation was assessed by quantitative immunohistology. Patients suffering from amyloidosis revealed a significant poor prognosis with proof of intramyocardial inflammation in contrast to those without inflammation (log‐rank P  = 0.019). Re‐grouping of patients indicated AL amyloidosis to have a significant impact on all‐cause mortality (log‐rank P  = 0.012). The detailed subgroup analysis showed that patients suffering from AL amyloidosis with intramyocardial inflammation have a significantly worse prognosis compared with AL amyloidosis without inflammation and ATTR with or without inflammation, respectively (log‐rank P  = 0.014, contingency Fisher's exact test, P  = 0.008). Conclusion: Our study reports for the first time a high incidence (48.1%) of intramyocardial inflammation in a series of patients with EMB‐proven cardiac amyloidosis and could show that in patients with AL amyloidosis, intramyocardial inflammation correlated significantly with increased mortality. Our data have a direct clinical impact because one can hypothesize that additional immunomodulating/anti‐inflammatory treatment regimens in patients with biopsy‐proven inflammation of heart muscle tissue could be beneficial for patients suffering from cardiac AL amyloidosis.